Modern times [videorecording (DVD)] - Chaplin, Charlie, 1889-1977 (Criterion collection, 2010)
When his boss demands more speed and efficiency, Chaplin goes crazy from his repetitious assembly line job. Primarily a silent film with music and sound effects, but occasional voices emanate from radios and television screens.